1990
DOI: 10.1007/bf01850975
|View full text |Cite
|
Sign up to set email alerts
|

The use of magnetic resonance imaging for the diagnosis of fetal intracranial anomalies

Abstract: While fetal cranial sonography has been used for the sensitive detection of ventriculomegaly, ancillary imaging techniques may be needed for precise delineation of structural abnormalities. This report outlines the radiologic and clinical results using maternal magnetic resonance imaging (MRI) in ten patients with suspected fetal intracranial anomalies. Imaging was accomplished at 17-39 weeks gestational age, using spin-echo, a multislice technique with intramuscular morphine sulfate for sedation. In four case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It also helped to characterize ventricular dilatation and anomalies of the corpus callosum and posterior fossa [27]. To date, only one small study from 1990 has tangentially looked at the application of fetal MRI to myelomeningocele [36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also helped to characterize ventricular dilatation and anomalies of the corpus callosum and posterior fossa [27]. To date, only one small study from 1990 has tangentially looked at the application of fetal MRI to myelomeningocele [36]. …”
Section: Discussionmentioning
confidence: 99%
“…To date, 15 studies encompassing 934 fetal MRI cases (including this review) have been reported using scanners at field strengths of 1.5 T or less, and no harmful effects to the developing fetus have been documented. This includes one large study of 400 fetuses, and another involving 20 children with a 3-year follow-up [1, 3, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37]. The second problem, motion artifact, has often been dealt with in the past by the administration of sedatives or paralytics, but the use of these agents obviously increases the complexity and risk of the study.…”
Section: Discussionmentioning
confidence: 99%
“…One area in which MRI has proven to be especially beneficial is in evaluation of the fetal CNS (61)(62)(63)(64)(65)(66)(67). Sonographic evaluation of the fetal CNS is limited by: 1) the nonspecific appearance of some anomalies; 2) technical factors that limit resolution of the side of the brain near the transducer; 3) ossification, which obscures visualization of posterior fossa structures; and 4) subtle parenchymal abnormalities that frequently cannot be visualized with ultrasound (68).…”
Section: Cns Anomaliesmentioning
confidence: 99%
“…The diagnosis of these pathologies can easily be made with magnetic resonance imaging. The sisterna magna measurements larger than 10 mm may suggest Dandy-Walker malformation, Dandy-Walker variant (partial wermian agenesis), mega sisterna magna, cerebellar hypoplasia or arachnoid cyst (47,48). In the Dandy-Walker malformation there are vermis agenesis, dilatation of the fourth ventricle and elongating of the posterior fossa below the tentorium.…”
Section: Holoprozencephalymentioning
confidence: 99%